Social Bonds as an Instrument of Responsible Investment - Yuliya Yelnikova; Irina Golochalova (Financial Markets, Institutions and Risks)
Research dedicated to structuring the scientific sphere in social bonds as an instrument responsible investing. The purpose of the paper is to form an information and bibliographic field of research of social bonds as tools of VI and their statistical support in the context of a new type of SIP. It was found that social bonds as a public-private partnership aimed at achieving financial, social impact and influence on the development fully meets the criteria of the VI instrument, but is studied primarily in the context of the empirical. The reason for this is the fact that the keys were based on practical use, and there is a large number of publications on a wide range of topics in the Scopus database without specifying the sound supply of the arms of 11,207 documents. A donation for the analysis of the informational-biometric field of social oblasts as for the tool BI will be received from the number of publications indexed by Scopus (Elsevir). Hours of progress for analysis at the end of 15 years (2005-2020 years). As for the research methodology, it is quite broad and includes built-in tools for analyzing the publication of the Scopus database, which provide a general idea of the information and bibliometric field of social bonds, software bibliometric analysis based on VOSviewer 1.6.15 for clustering analyzed publications with subsequent visualization, Google tools Trends and Google Data to study Internet search activity information and statistics for this tool. The first two methods allowed to analyze the publishing activity on the studied tools in academic circles on the leading base of scientific publications. The third is to describe the current trends in the development of information and statistical support of social bonds. The application of these methods for structuring the scientific sphere of social bonds allowed to justify its status – as one that is formed and requires additional information and statistical support.